Should High‐grade Extraosseous Osteosarcoma Be Treated With Multimodality Therapy Like Other Soft Tissue Sarcomas?. Issue 11 (November 2015) - Fan, Zhengfu; Patel, Shreyaskumar; Lewis, Valerae O.; Guadagnolo, Ashleigh B.; Lin, Patrick P.
Abstract: Background: Extraosseous osteosarcoma is rare, and the most appropriate therapy is unclear because there are few studies regarding its treatment. The effectiveness of radiation and chemotherapy remains uncertain owing to conflicting results in previous reports. Questions/purposes: To review our experience with contemporary multimodality treatment, we asked: (1) What is the disease‐specific survival and local relapse‐free survival? (2) Does American Joint Commission on Cancer (AJCC) stage, tumor size, or location relate to disease outcome? (3) Does radiation therapy improve local control or survival? (4) Do doxorubicin and ifosfamide improve local control or survival? Methods: Between 1990 and 2012, we treated 40 patients for localized, high‐grade extraosseous osteosarcoma. In this retrospective study, we could determine the status of 36 patients (90%) either to death or for a minimum of 24 months of followup; four (10%) were lost to followup before 24 months. There were 11 patients with AJCC Stage IIA and 25 with Stage III disease. All patients underwent wide surgical excision. Of the patients with Stage IIA disease, four received radiation and none received chemotherapy. Of the patients with Stage III disease, six received radiation, seven were treated with chemotherapy, and six received radiation and chemotherapy. During the study period, high‐dose doxorubicin and ifosfamide was the preferred chemotherapy regimen for patients younger than 60 years with normal cardiac and renal function. Local relapse‐free survival and disease‐specific survival were determined by Kaplan‐Meier analysis using a prospectively maintained institutional database supplemented by information from the institutional tumor registry. The Cox proportional hazard model was used to determine the effect of various factors on local recurrence and patient survival. Results: At 5 years, local relapse‐free survival was 47% (95% CI, 27%‐64%), and disease‐specific survival was 53% (95% CI, 35%‐68%). In multivariate analysis, AJCC stage, which depends on tumor size, was the strongest predictor of local relapse‐free survival (hazard ratio [HR] = 0.17, p = 0.02), while tumor depth was the best predictor of disease‐specific survival (HR = 5.6, p = 0.02). Radiation improved local relapse‐free survival (HR = 0.30, p = 0.03) but not disease‐specific survival in multivariate analysis. A regimen of doxorubicin and ifosfamide was associated with better local relapse‐free survival for patients with Stage III disease (HR = 0.16, p = 0.04) but not disease‐specific survival (HR = 0.32, p = 0.08). Conclusions: With the limited number of patients in our study, it appears that extraosseous osteosarcoma behaves differently than osteosarcoma of bone. Multimodality treatment that includes doxorubicin and ifosfamide‐based chemotherapy, radiation, and surgery may be a valid therapeutic strategy for Stage III disease, but larger, prospective studies will be needed to verify our preliminary observations. Level of Evidence: Level III, therapeutic study.